Qualitative Study of Decision Making Family Selection of Mother’s Contraception - Anggraeni, Widya; Idayanti, Titiek; Fauziah, Rahma (Universitas Islam Lamongan, 2025)
The purpose of this study to determine and demonstrate the theory about the factors that influence family decisions on the selection of contraception in postpartum maternal health center Gayaman Mojokerto. This research is a descriptive study using qualitative methods approach. Technique of data collection by deep interviews. Informant or informants in this research five pairs of husband and wife who own characteristics and work the same tribe. The research was conducted by using a tape recorder and aided by assistant interview. In analyzing the data is done by data reduction, categorization of data, displaying of data and then draw the conclusions..The result of each informant the interview be the amplifier for the writer in validating the theory and explore what is purpose of the writer in this research. The result the form of the expression from every interviews the informant appear and explained in the chapter results of interviews. It can be concluded that the factors that influence the family decision making to election of contraceptives are environmental factor, individual differences factor, health factor, and pair of contraceptive factor method. While for the process of psychology factor the researcher could not prove the that these factors include the factor that influence the the decision making to election of contraceptives are health factor. The factor most instrumental to influence in decision making to election factor of contraception is contraception method, where it concerns the social and economic factor.